TRANSFORMASI PENDIDIKAN AGAMA ISLAM DALAM SEJARAH PERADABAN ISLAM MELAYU: DARI TRADISI KEILMUAN KLASIK MENUJU MODERNISASI PENDIDIKAN - Sri Juwita; Donna Takrim; Maryamah; Zulhijra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses the transformation of Islamic religious education in the history of Malay Islamic civilization from classical scholarly traditions to the modernization of education. Initially, Islamic education in the Malay world developed through traditional educational institutions such as pesantren, surau, and dayah, which focused on the study of classical Islamic texts and the development of moral and spiritual values. With the emergence of modernization, the Islamic education system experienced significant changes in terms of curriculum, learning methods, and institutional management. This study employs a qualitative approach using library research by analyzing various relevant sources such as books and scholarly articles. The findings reveal that the transformation of Islamic education in the Malay world has occurred through the integration of classical scholarly traditions with modern educational systems. This integration is reflected in the combination of religious and general subjects within the curriculum, the development of more adaptive learning methods, and the utilization of technology in educational practices. Therefore, Islamic education in the Malay region has been able to maintain traditional values while adapting to contemporary developments.